2022
DOI: 10.1001/jamaophthalmol.2022.1357
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Visual Acuity and Residual Retinal Fluid Following Intravitreal Anti–Vascular Endothelial Growth Factor Treatment for Neovascular Age-Related Macular Degeneration

Abstract: IMPORTANCEThe association between residual subretinal fluid (SRF) and intraretinal fluid (IRF) and visual acuity following anti-vascular endothelial growth factor (VEGF) treatment is not well understood.OBJECTIVE To examine the association of residual retinal fluid, SRF, and IRF with visual acuity following anti-VEGF treatment in patients with neovascular age-related macular degeneration (nAMD).DATA SOURCES A systematic literature search was performed from January 2005 to August 2021 using Ovid MEDLINE, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…Most eyes (274/294 eyes, 93.2%) had chronic retinal fluid and were switched from other anti-VEGF agents because of insufficient response with 19.97 ± 13.87 mean number of anti-VEGF injections, which might have affected the visual recovery and restoration of photoreceptors. Several studies have reported an association between the presence of residual fluid after the anti-VEGF injection and VA, suggesting that persistent IRF is related to poor visual outcomes [28][29][30]. Although most included eyes had longstanding residual fluid, the baseline BCVA (logMAR) was 0.518 ± 0.356, similar to those recruited in pivotal studies (mean baseline BCVA: 60.6 letters [HAWK] and 61.2 [HARRIER]) and better than those in other real-world studies.…”
Section: Short-termmentioning
confidence: 99%
“…Most eyes (274/294 eyes, 93.2%) had chronic retinal fluid and were switched from other anti-VEGF agents because of insufficient response with 19.97 ± 13.87 mean number of anti-VEGF injections, which might have affected the visual recovery and restoration of photoreceptors. Several studies have reported an association between the presence of residual fluid after the anti-VEGF injection and VA, suggesting that persistent IRF is related to poor visual outcomes [28][29][30]. Although most included eyes had longstanding residual fluid, the baseline BCVA (logMAR) was 0.518 ± 0.356, similar to those recruited in pivotal studies (mean baseline BCVA: 60.6 letters [HAWK] and 61.2 [HARRIER]) and better than those in other real-world studies.…”
Section: Short-termmentioning
confidence: 99%
“…The cohort of patients with a maximum extension interval of 4 weeks likely had persistent choroidal neovascularization requiring treatment, which may be protective against macular atrophy [12]. In other studies, patients with nAMD and persistent residual SRF were found to have better BCVA at last study observation when compared to those without residual SRF [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of baseline BCVA, inability to discern between persistent and transient IRF/SRF, and small sample sizes in these subgroups limit the inferences of our findings. Other studies have suggested that SRF can be protective for photoreceptors and can prevent macular atrophy [13, 14, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, numerous clinical studies have shown that anti-VEGF agents have achieved good therapeutic effects in inhibiting pathological ocular neovascularization [20][21][22] . Despite the extensive clinical applications, there were still several deficiencies that have not been filled, such as frequent injection or drug resistance 23,24 . In this study, we designed and synthesized a new multi-target kinase inhibitor, DCZ19931, which could suppress ocular neovascularization by targeting endothelial angiogenic effects.…”
Section: Discussionmentioning
confidence: 99%